Industrial Apprenticeship Model Based on Work-Based Learning for Pre-service Teachers in Automotive Engineering - Suyitno, Suyitno; Kamin, Yusri; Jatmoko, Dwi; Nurtanto, Muhammad; Sunjayanto, Edi (Frontiers in Education, 2022)
The low vocational competence of vocational teachers has become an essential issue in the last few decades. This problem is due to the lack of actual work experience in the industry for vocational teachers. One of the vocational skills improvement programs that are considered adequate is the industrial apprenticeship program. Many studies discuss apprenticeships, but there are still limited studies that examine effective apprenticeship programs to improve the competence of pre-service teachers at automotive engineering Vocational High Schools. Therefore, this study aims to determine the development of a Work-Based Learning (WBL)-based industrial apprenticeship model and its effectiveness to improve the competence of pre-service teachers at Vocational High Schools in the field of automotive engineering. This study uses an Education Research and Development (R&D) approach and involves two campuses in Central Java-Indonesia. There were 20 pre-service vocational teachers and three industry parties involved in the preliminary study. The preliminary study aims to obtain information about the problems and needs of the apprenticeship model. Furthermore, there were 60 pre-service vocational teachers and 12 industry parties involved in a follow-up study to test the effectiveness of the apprenticeship model. The sampling technique used is purposive sampling. The study results revealed that the WBL-based industrial apprenticeship model for pre-service vocational teachers in the automotive engineering field was considered feasible. In addition, the implementation of a WBL-based industrial apprenticeship can improve the competence of pre-service automotive engineering teachers, which includes knowledge, attitudes, and skills in the field of automotive engineering. The results of this study have implications for vocational education practitioners, especially higher education that organizes teacher education programs, to apply this apprenticeship model in preparing pre-service vocational teachers. This is because the WBL-based industrial apprenticeship model for pre-service vocational teachers plays a vital role in improving vocational skills for pre-service vocational teachers.